Hospital Legal Responsibility for Unlawful Acts in Health Services: A Normative Juridical Analysis of Vicarious Liability and Central Responsibility Under Indonesian Health Law - Zaini Abdillah; N. Ike Kusmiati (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Hospital-related patient safety incidents and medical negligence disputes have increased pressure on Indonesia's health governance system, revealing a significant legal gap. Article 193 of Law No. 17 of 2023 limits hospital liability to vicarious liability for health personnel, yet differing interpretations raise questions about whether hospitals also bear central responsibility for duty of care and facility management. Objective: It aims to analyze hospital legal liability for unlawful acts in health service provision, focusing on three aspects: the scope of hospital liability, the application of compensation, and the legal basis for unlawful acts. Methods: It employs a descriptive-analytical method with a normative-juridical approach, relying on primary, secondary, and tertiary legal materials, complemented by interviews. Data were analyzed qualitatively without statistical methods. Results: The findings reveal that hospital liability extends beyond vicarious liability to include centralized institutional responsibility for duty of care and facilities. Compensation for unlawful acts is applied analogically from Articles 1243–1248 of the Civil Code, covering costs, losses, and interest, including both material and immaterial damages, provided there is no contributory negligence by the patient. Furthermore, liability for unlawful acts under Articles 1365–1367 of the Civil Code should be directed not at the hospital as an entity, but at the controlling legal body, such as a company (PT) or government institution. Conclusion: Indonesian hospital liability law requires harmonization. Article 193 should be interpreted broadly to include both forms of responsibility, and legal reforms are needed to clarify liability and improve mechanisms for patient compensation.